2021
DOI: 10.1002/asjc.2553
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive finite‐time control for turbo‐generator of power systems with prescribed performance

Abstract: Control of turbo-generator is facing great challenges resulting from more renewable energies injected into power systems, and it is still a challenging task to improve the accuracy and convergence speed when the operation point changes. In this paper, an adaptive finite-time controller design is proposed for turbo-generators in the presence of bounded disturbances and unknown system dynamics. Compared with existing methods, the finite-time stability rather than asymptotic stability or uniformly ultimately boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…This paper considers a model of the turbo-generator in a single-machine infinite bus (SMIB) power system, which is described by [1,12,36]. The SMIB system with a turbo-generator is showed in Figure 1.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper considers a model of the turbo-generator in a single-machine infinite bus (SMIB) power system, which is described by [1,12,36]. The SMIB system with a turbo-generator is showed in Figure 1.…”
Section: System Descriptionmentioning
confidence: 99%
“…The main work of this paper is to optimize [12]. In this paper, the result of [12] is optimized, the chattering problem caused by the sliding mode control method is eliminated, and the dead zone of the actuator is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, there exists a compromise between multiple indices including prescribed performance and other control qualities. In practical applications, we should make a reasonable tradeoff between these indices [117,[157][158][159][160][161][162][163][164][165][166][167][168][169].…”
Section: The Approach For Handing the Perturbations Of Tracking Errorsmentioning
confidence: 99%
“…In (Liang et al, 2021) an FTC was suggested for turbo-generators in the existence of limited disturbances and unidentified scheme dynamics. The constant boundaries on the system states and multi-terminal sliding mode were suggested to improve the transient performance.…”
Section: Finite-time Control: Approaches and Reviewmentioning
confidence: 99%